Does the addition of chlorhexidine to glass ionomer cements influence its antimicrobial effect and survival rate? A systematic review - da Mota Martins, V.; Paranhos, L. R.; de Oliveira, M. N.; Maia, L. C.; Machado, A. C.; Santos-Filho, P. C. F. (European archives of paediatric dentistry, 2022)
Purpose To evaluate the influence of the addition of chlorhexidine on the antimicrobial effect and on the survival of restorations performed with glass ionomer cement. Methods Nine databases were used to search for randomized clinical trials that compared the survival rate and the antimicrobial effect of glass ionomer cement (GIC) restorations with and without the incorporation of chlorhexidine (CHX), without restrictions on year or language. Cochrane Collaboration’s Risk of Bias 2 was used to assess the risk of bias. The GRADE approach was used to assess the certainty of evidence. Results From 593 studies found, seven met the inclusion criteria. The concentration of CHX varied between 0.5 and 2%. In general, the addition of CHX to GIC promoted reductions in Streptococcus mutans and Lactobacillus acidophilus burdens when compared to those without CHX. No study showed a difference in the survival of restorations between GIC with CHX and conventional GIC. Individual risk of bias varied from low to high and the certainty of evidence was classified as very low. Conclusions Based on a very low level of certainty, the evidence suggests that the incorporation of CHX in GIC might improve the antimicrobial effects for a short time, in addition to having little influence on the survival of the restoration.